Entrepreneurial pathways and technological innovation: A theoretical framework for understanding the dynamics of technology-driven venture creation - GOUMGHAR Said; OUAHRAOUI Fatima; FIKRI Majda; ZOUBIR Faical (African Scientific Journal, 2025)
Abstract This paper develops an integrative theoretical framework to account for the dynamics of technology-driven venture creation. Grounded in a conceptual methodology that draws on an extensive review of the relevant literature, it seeks to move beyond fragmented accounts of entrepreneurship, innovation, and context. The framework synthesizes three central constructs, technology entrepreneurship, the entrepreneurial ecosystem, and digital transformation. It conceptualizes the entrepreneurial process as a dynamic and non-linear trajectory informed by effectual reasoning, while demonstrating how digital transformation and ecosystem resources function as enabling forces. Central to this model is the proposition of a co-emergent relationship in which entrepreneurial action, technological change, and environmental resources are mutually constitutive. This conceptualization offers a more refined understanding of how opportunities are identified, constructed, and exploited within technology-intensive settings. Several theoretical contributions emerge. For entrepreneurship research, the framework provides a holistic and context-sensitive lens that situates entrepreneurial dynamics within technological and systemic environments. For innovation studies, it reaffirms the entrepreneur’s role as the principal agent of technological change and diffusion. Practical insights also follow. Entrepreneurs are encouraged to adopt adaptive, effectual strategies that capitalize on digital tools and ecosystemic resources rather than rigid causal planning. Policymakers are urged to design multifaceted entrepreneurial ecosystems rather than isolated support measures. For educators, the framework highlights the need for curricula that cultivate adaptability and technological literacy. Collectively, this work establishes a robust conceptual foundation for future empirical inquiry and guidance for navigating the complexities of technology-driven entrepreneurship in the digital era. Keywords : Technology Entrepreneurship, Entrepreneurial Ecosystems, Digital Transformation, Innovation, Venture Creation